PENGOLAHAN SAMPAH RUMAH TANGGA MELALUI INOVASI TEBA MODERN SEBAGAI SOLUSI PENGELOLAAN LINGKUNGAN BERKELANJUTAN - Putu Atim Purwaningrat; Luh Nik Oktarini; I Putu Indrayana Putra; I Made Abdi Arnatayasa; Ni Kadek Citra Dewi Yasti (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Waste management in Penatih Dangin Puri Village faces a serious challenge due to an unsustainable conventional system, leading to waste accumulation and negative environmental impacts. This program aims to present a solution through the TEBA (Tempat Ember Bakteri / Bacterial Bucket Site) Modern Innovation. The primary focus is on managing organic waste through the creation of Teba Modern units. This activity intends to increase public awareness regarding environmental cleanliness and provide practical examples of Teba Modern construction to mitigate the negative impact of poorly managed organic waste. The implementation method comprises two main steps. First, socialization with the community to provide understanding of the Teba Modern concept, its benefits, and how to process organic waste into compost. Second, the construction of a model Teba Modern unit to inspire the community to implement this concept in their respective homes. The results of this community service activity show an increase in public awareness of the importance of organic waste management, a heightened concern among residents for environmental cleanliness, and a deeper understanding of the processes involved in independent waste management and composting using Teba Modern.